STUDY ON LOAD EQUIVALENT METHOD AND LOAD SPECTRUM OF THE BOOM OF LOADER - LIANG Jia; SONG XuDing; GAO XiaoWei; LV PengMin; ZHANG Lei (Jixie qiangdu)
Based on the measured load of the 5 t loader working device,the method of solving the load with the attitude change to the local coordinate system of the boom has been studied and the MATLAB software to write the corresponding data processing program has been sued to obtain the loader arm under the fixed attitude of the load time course. The dangerous position of the boom is determined by the static analysis,and the equivalent external load of the boom is obtained by the stress equivalent principle of dangerous cross section position. On this basis,the boom load spectrum is compiled. The results provide a reference for the fatigue test and anti-fatigue design of the boom.